2019
DOI: 10.3906/biy-1904-37
|View full text |Cite
|
Sign up to set email alerts
|

Keratin 14 is a novel interaction partner of keratinocyte differentiation regulator: receptor-interacting protein kinase 4

Abstract: The epidermis is a stratified epithelium that protects the organism against environmental insults. The maintenance of the epidermis is provided by sustained proliferation and differentiation of the keratinocyte stem cells localized to the basal layer of the epidermis (Fuchs and Nowak, 2008; Blanpain and Fuchs, 2009). As keratinocyte stem cells commit to differentiate, they cease to proliferate and start to move upward to form suprabasal layers, including spinous, granular, and stratum corneum with different bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
1
10
0
1
Order By: Relevance
“…Finally, the present study can clarify why zebrafish blastema regeneration is epithelial-dependent (Wang et al, 2012;Zhang et al, 2015), and how undergo EMT (Lepilina et al, 2006). Our data showed that the epithelial-predominant keratin could help cell to bridge mechanosignaling between extracellular-cytoplasmic signal transductions and histone modifications-mediated chromatin remodeling, thus supporting the view that the keratin could modulate IF-cytoskeleton organization, interact with focal adhesions and cell-surface molecules (Quinlan et al, 2017;Sumer et al, 2019). By in vitro culture of zebrafish embryonic fibroblast cells, we demonstrated that the keratin 5 network could modulate H3K9Ac/Me3 chromatin state and expression of three core blastema tissue specific genes through the noncanonical BMP4 signaling pathway (Fig.5C).…”
Section: Discussionsupporting
confidence: 75%
“…Finally, the present study can clarify why zebrafish blastema regeneration is epithelial-dependent (Wang et al, 2012;Zhang et al, 2015), and how undergo EMT (Lepilina et al, 2006). Our data showed that the epithelial-predominant keratin could help cell to bridge mechanosignaling between extracellular-cytoplasmic signal transductions and histone modifications-mediated chromatin remodeling, thus supporting the view that the keratin could modulate IF-cytoskeleton organization, interact with focal adhesions and cell-surface molecules (Quinlan et al, 2017;Sumer et al, 2019). By in vitro culture of zebrafish embryonic fibroblast cells, we demonstrated that the keratin 5 network could modulate H3K9Ac/Me3 chromatin state and expression of three core blastema tissue specific genes through the noncanonical BMP4 signaling pathway (Fig.5C).…”
Section: Discussionsupporting
confidence: 75%
“…As the most abundant skin cell type, EpD accounted for 37.96% (9201 cells) of all skin cells, which could be divided into nine different clusters, including three basal cell types (EpD_Basal1–3) majorly expressing basal epithelium markers KRT5, KRT14, ITGA6, and ITGB1; four epithelial differentiated cell types (EpD_Spinous, EpD_Granualr/spinous, EpD_Granular, EpD_Corneum) majorly recognized by epithelial differentiation marker KRT10, KRT1, and GRHL1 (ref. 20 23 ); sebaceous gland (EpD_SG) expressing APOC1, ACSL5, ABCC3 (ref. 24 ); follicles (EpD_Foli) expressing CD200, SOX9, KRT19 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…Newly produced cells gradually differentiate and mature into keratinocytes, move toward upper layers and comprise the epidermal tissue [ 37 ]. To examine whether GREM2 expression and the differentiation level in the epidermis are correlated, immunohistochemistry was performed against GREM2, an epidermal undifferentiation marker KRT14 and an epidermal differentiation marker KRT10 [ 38 , 39 ] on human skin sections (n = 14), and expression levels were analyzed. Since our previous study showed that GREM2 expression levels prominently varied among elderly individuals [ 18 ], we examined skin samples from the elderly (65–89 years of age).…”
Section: Resultsmentioning
confidence: 99%